Leptospira Seroprevalence in Capybaras from a Brazilian Urban Area - Tonin, Alexandre Alberto; Krawczak, Felipe da Silva; Noll, Jéssica Carolina Gomes; Tochetto, Camila; Martins, Jorge Luiz Rodrigues; Badke, Manoel Renato Teles; Labruna, Marcelo Bahia; Silva, Aleksandro Schafer Da (Acta Scientiae Veterinariae, 2016)
Background: Leptospirosis remains the most widespread zoonotic disease in the world. As a clinical entity it is strongly associated with regional occupational and environmental exposures. While the exact global disease burden remains unknown, recent estimates by the leptospirosis Burden Epidemiology Reference Group (LERG) at the World Health Organization have set the number of human cases of severe leptospirosis to over 500,000 per year. This number almost certainly represents an under-representation due to poor surveillance and difficult diagnosis. Leptospira spp. belong to the order Spirochaetales, family Leptospiraceae, composed by 13 pathogenic Leptospira species with more than 260 serovars. Wildlife species are commonly considered to be important epidemiological carriers, mainly because of their frequent reactivity to Leptospira serovars native to their habitat. Capybara (Hydrochaeris hydrochaeris), a known leptospirosis host, is a widespread species in South America. However, reports regarding the importance of this animal in the epidemiology of leptospirosis are rare. Therefore, the objective of this study was to report the results of leptospirosis serological survey of capybaras from a residential park area in southeastern Brazil. Materials, Methods & Results: A total of 172 capybaras were sampled at Itú Municipality, state of São Paulo, southeastern Brazil, from December 2012 to May 2013. Sera samples were examined for Leptospira antibodies by the microscopic agglutination test (MAT), using live antigens grown in liquid medium (EMJH). A complete panel of 7 serogroups (including 10 reference serovars) was used as antigens: serogroup Sejroe (serovars Hardjo and Wolffi), serogroup Grippotyphosa (serovar Grippotyphosa), serogroup Canicola (serovar Canicola), serogroup Icterohaemorrhagiae (serovars Icterohaemorrhagiae and Copenhageni), serogroup Australis (serovars Australis and Bratislava), serogroup Pomona (serovar Pomona), and serogroup Autumnalis (serovar Butembo). As a results, 46 (26.75%) were serologically positive: 29 (63.05%) for serogroup Sejroe, 7 (15.22%) for serogroup Icterohaemorrhagiae; 9 (19.56%) were seropositive for serogroups Sejroe and Icterohaemorrhagiae; and 1 (2.17%) was positive for serogroups Sejroe and Grippotyphosa. Discussion: L. interrogans sensu stricto is responsible for the most frequent and severe cases of human and animal leptospirosis. Considering the results of our serological survey, it is important to reinforce that in tropical countries, mainly Brazil, India, Thailand, Vietnam, Australia and Barbados, serovars belonging to the Icterohaemorrhagiae serogroup (Icterohaemorrhagiae and Copenhageni) are generally the most prevalent. Therefore, the report of different serogroups in capybaras (as observed in our study) it is an important observation reported. Human leptospirosis is usually due to serovars that are maintained by the animal populations of a region, which spread the bacterium on the environment; thus, it may represent an important additional risk factor for human population. Our study identified a greater serum reactivity to strains that belongs to serogroup Sejroe. In Brazil this serogroup is highly predominant in livestock; thus, our main hypothesis is that some animals were contaminated with Sejroe serovars when they were at their natural habitat and, once in the park, they maintained these serovars through cross transmission. Therefore, based on our results, it was possible to observe a significant prevalence of serovars belonging to serogroup Icterohaemorrhagiae, and there was also a high prevalence of samples positive to serogroup Sejroe. Thus, our serologic survey showed that capybaras living in an urban area could represent a risk factor for leptospirosis for the human population eventually exposed.